SAT0345 Lifestyle, Clinical and Psychosocial Predictors of Good Response to Methotrexate Therapy in the Rheumatoid Arthritis Medication Study (RAMS). (9th June 2015) - Sergeant, J.C.; Hope, H.F.; Anderson, J.; Barton, A.; Hyrich, K.L.; Verstappen, S.M.M.
Abstract : Background: Methotrexate (MTX) is the disease modifying drug of first choice for most patients with rheumatoid arthritis (RA). However, response to MTX varies and attempts to identify predictors of response have proved inconsistent. Objectives: To evaluate potential lifestyle, clinical and novel psychosocial predictors of response to MTX in the Rheumatoid Arthritis Medication Study (RAMS), a cohort of RA patients commencing MTX therapy for the first time. Methods: RAMS is a multi-centre observational study recruiting RA patients from across the UK who are ≥18 years old and starting MTX for the first time. Predictors of response to MTX are acquired via questionnaires and from case notes at baseline 3, 6 and 12 months after MTX commencement. Response to treatment was defined at 6 months using the EULAR definition of good response: disease activity score-28 (DAS28) ≤3.2 and reduction in DAS28 from baseline >1.2. Associations between good response at six months and baseline measures of body mass index (BMI), smoking status (current/former/never), alcohol intake, symptom duration, DAS28, functional disability (Health Assessment Questionnaire, HAQ), C-reactive protein (CRP), creatinine, rheumatoid factor (RF), socioeconomic status (Index of Multiple Deprivation, IMD), anxiety and depression (Hospital Anxiety and Depression Scale, HADS), beliefs about medicines (Beliefs about Medicines Questionnaire, BMQ) and illness representation (Brief Illness Perceptions Questionnaire (BIPQ)) were assessed using chi-square or Mann-Whitney tests and adjusted for age and sex using multiple logistic regression. Results: Complete data on baseline predictors and response at six months was available on 460 participants: 338 female (73%), median age 60 (IQR 48-68) years, median symptom duration 9 (IQR 5-30) months. 130 participants (28%) were good responders. Baseline measures for good responders and non-good responders, together with group comparisons and adjusted odds ratios are shown in Table 1 . Good response was negatively associated with BMI, current smoking and anxiety and depression, and positively associated with baseline DAS28, elevated CRP, RF positivity and positive illness representation. Conclusions: Lifestyle, clincial, and novel psychosocial factors were found to be predictors of response to MTX at six months. Notably those with higher values of baseline disease activity and serological and inflammatory markers were more likely to be good responders, perhaps reflecting a greater potential to improve. Prediction models of individual MTX response in RA may need to consider the potential role of such factors in personalising treatment decisions. Disclosure of Interest: None declared